Study on the production of high 3HV content PHBV via an open fermentation with waste silkworm excrement as the carbon source by the haloarchaeon Haloferax mediterranei - Cai, Shuangfeng; Wu, Yaran; Liu, Runjie; Jia, Hongzhe; Qiu, Yunxiao; Jiang, Min; Ma, Yuwen; Yang, Xingxu; Zhang, Siyu; Zhao, Yan; Cai, Lei (Frontiers in Microbiology, 2022)
Silkworm excrement is hard to be degraded or bio-utilized by environmental microorganisms due to its high content of heavy metals and antimicrobial biomacromolecules in mulberry leaves. In traditional Chinese silk industry, the silkworm excrement results in environmental problems. In this study, the silkworm excrement after chlorophyll ethanol-extraction was researched. An open fermentation strategy was developed using the silkworm excrement as the sole or partial carbon source by haloarchaea to accumulate polyhydroxyalkanoates. As a haloarchaeon with strong carbon source utilization ability, Haloferax mediterranei was found to accumulate a certain amount of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) using waste silkworm excrement. The results showed that the addition of silkworm excrement into glucose based fermentation medium can significantly improve the production of PHBV. Using a mixture carbon source including the extract of silkworm excrement and glucose (with a 1:1 carbon content ratio), the yield of PHBV was 1.73 ± 0.12 g/L, which showed a 26% increase than that of fermentation without the silkworm excrement addition. When the NaCl content of medium was set to approximately 15%, fermentation without sterilization was performed using silkworm excrement as the carbon source. Moreover, the addition of the silkworm excrement extract could increase the 3-hydroxyvalerate (3HV) content of PHBV regardless of the sterilization or non-sterilization fermentation conditions. When using silkworm excrement as the sole carbon source, the 3HV content was as high as 16.37 ± 0.54 mol %. The real-time quantitative PCR results showed that the addition of the silkworm excrement could specifically enhance the expression of genes involved in the aspartate/2-ketobutyric acid pathway related to 3HV synthesis in H. mediterranei, and further analysis of the amino acid of the silkworm excrement suggested that the high content of threonine in the silkworm excrement might be the reason for the increase of 3HV content. Taken together, the success of non-sterile fermentation in hypersaline condition using haloarchaea implied a novel way to reuse the silkworm excrement, which not only reduces the production costs of PHBV, but also is conducive to environmental protection.